PENGARUH PENERAPAN SISTEM INFORMASI DATABASE RISET DAN PENGABDIAN MASYARAKAT (SIDR) DI LINGKUNGAN UNIVERSITAS INDONESIA - Qurrotin A’yunina; muhammad soleh; ari wibisono (Faculty of Computer Science Universitas Indonesia, 2015)
Sistem Informasi Database Riset dan Pengmas (SIDR) is an information system that saves the reseach and community service data in Universitas Indonesia. To evaluate the effectiveness of SIDR, it is ideal to gather data about the SIDR user’s responses. Consequently, in the present study, questionnaire method uses a 6-point Likert scale is applied to obtain that kind of information. In general, the results show that SIDR provides an effective means of creating and centralizing research and community service data for whole faculties in Universitas Indonesia.